SOCIAL CONSTRUCTION OF BOYHOOD IN SCHOOLS OF DELHI (Proceedings of the World Conference on Women’s Studies, 2018)
In the context of education, 'social system' refers to the internal organization and processes of education analyzed as a coherent unit which is distinguishable from other aspects of society. Education cannot be divorced from its social setting because those engaged in education are also the ones who carry with them the symbols and orientations that identify them as members belonging to distinct sections of society. Children bring with them a certain culture. They have learnt certain patterns of speech, certain habits and certain orientations to life from their family and neighborhood. Children do not drop their accent or style of dress soon after entering a school. These are often subtle yet deeply ingrained. Social background is relevant to the analysis of the relationship between education and socialization because it orients a child to enter into certain patterns of association, or to have certain responses to the school. Social background, however, is not the only factor. Peer relationships are equally important.
Keywords: Boyhood; Children; Society